DAMPAK STRATEGI REINFORCEMENT DAN PUNISHMENT DALAM PARENTING TERHADAP KEMAMPUAN ANAK MEREGULASI EMOSI DI ERA DIGITAL - Berta Charolina Balqis; Yanuar Akmal Alfaresi; Muhamad Afifuddin Ghozali; Budi Purwoko (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
The digital era presents new challenges for parents, particularly in managing children's gadget use and emotional regulation. This study explores the impact of reinforcement and punishment strategies on children's emotional regulation abilities in the digital age. Using a qualitative phenomenological approach, data were collected through in-depth interviews with 15 parents of children aged 7–12 years in urban areas. Thematic analysis identified patterns in parenting strategies and their influence on children's emotional regulation. Findings show that positive reinforcement, such as rewards for good behavior, fosters adaptive emotional management. Conversely, punishment, while effective in correcting behavior, may lead to negative emotional outcomes if applied excessively. Parents face significant challenges in limiting gadget use, which often impacts children's emotional regulation. A balanced parenting approach that combines positive reinforcement with structured gadget-use limits is crucial for improving emotional regulation. This study underscores the need for supportive and adaptive parenting strategies to navigate the challenges of the digital age.